Morphological and anatomical study of four Pyrrosia (Polypodiaeae) species from Rumbai forest, Riau Province, Indonesia - Nery Sofiyanti; Ayu Kumala Sari; Dyah Iriani; Rhozikhinul Mutrofin; Ikhwan Taufiq; Erwina Juliantari; Syafroni Pranata (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sofiyanti N, Sari AK, Iriani D, Mutrofin R, Taufiq I, Juliantari E, Pranata S. 2021. Morphological and anatomical study of four Pyrrosia (Polypodiaeae) species from Rumbai forest, Riau Province, Indonesia. Biodiversitas 22: 4905-4914. Pyrrosia is one of genera in Polypodiaceae that is commonly distributed at Riau Forest, Indonesia. However, the detailed morphological characteristics and anatomical study of Pyrrosia in this region is scanty. This study was aimed to characterize the morphology and anatomy of four Pyrrosia species (P. angustata, P. lanceolata, P. nipoboloides and P. piloselloides) from Rumbai Forest, Riau Province. All of the specimens were collected in the field. Morphological characters were examined in detail. Anatomical preparation was conducted using the paraffin method. The specimens were then observed and photographed using a light microscope. Principal Component Analysis had been carried out using a total of 52 morphological and anatomical characters. The result showed the morphological variation among the species, especially on the shape of sterile lamina and sori characteristics. Anatomically, the examined species showed variations in outline shape in the transverse section of rhizomes and stipes, schelerenchymatous sheath and strand, as well as number of meristele. The PCA results showed that only three characters (shape of sterile laminae, base of sterile laminae, and upper surface color of sterile laminae) have eigenvalue over 1.00 and together these explain 100% of the total variability of the data. The anatomical data in this study is reported for the first time on Pyrrosia from Riau province.